Artificial Intelligence-Based System Tools and Their Impact on The Lawyers’ Practice - Farouk, Aisha Dawaki; Fajar, Mukti (Jurnal Penegakan Hukum dan Keadilan, 2024)
This study focuses on artificial intelligence (AI)-based system tools and their impacts on the lawyer's practice. With the emergence of technology and its rapid development in the field of sciences, progress can be seen in the different sectors, including the legal profession. Traditionally, only licensed lawyers practice law, but that traditional notion has begun to change with the coming of technology. AI-based system tools were changing how lawyers practice law is being done. Legal information can now be analyzed through network analysis and machine learning (ML) systems. The study adopted an empirical type of research, using a qualitative and quantitative methodological approach to gather and analyze its data. Primary data was collected directly from the targeted respondents, while the secondary data were collected from relevant literature in libraries such as journals, books, newspapers, articles, and online publications. The data collected was analyzed using a frequency distribution table, pie chart, and simple percentage. The study highlighted that 58% agreed that AI was changing and impacting how lawyers practice law. The result showed that 50.9% were aware of the AI-based system tools to automate or assist lawyers in law practice.